THE INFLUENCE OF CAPITAL ADEQUACY, FUND TO ACCOUNT FOR DEPOSIT AND NON-PERFORMING ACCOUNT OF RETURN ON ASSETS IN PT. TIMELINE OF BANK JABAR BANTEN SHARIA BANK (2015-2023) - Alli, Kurnia Fatimah (Komitmen: Jurnal Ilmiah Manajemen, 2025)
Banks play an important role in a nation's economic development by acting as a financial intermediary connecting spare funds with those in need of capital. Islamic banks, like any financial institution, face financial risks in their operations and financial activities. A high-performance company is often characterized by its ability to achieve high profits at low costs. All business activities, including banking, involve various risks, especially financial risks that affect profits and paying obligations. This study examines how capital adequacy (CA) affects Return on Assets (ROA) and Funding Ratio (FDR) as well as the effect of Non-Performing Financial Ratio (NPF) on these metrics. A descriptive method was used with a quantitative method using secondary from the financial statements of PT. Bank Jabar Banten Syariah (2015-2023) accessed through their website. The results show partial effects.